2020
DOI: 10.21203/rs.2.12073/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outcomes after traffic injury: mental health comorbidity and relationship with pain interference

Abstract: Background: Mental health symptoms, like depressive mood (DM) and post-traumatic stress (PTS), and pain interference (PI) with daily functioning often co-occur following traffic injury and their comorbidity can complicate recovery. This study aimed to map the course and overlapping trajectories of mental health symptoms, and associations with PI in a traffic injury population. Methods: In total, 2019 adults sustaining minor-to-moderate traffic injury were recruited within 28 days post-injury and assessed using… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…In addition, pre‐MVC lifetime comorbid probable PTSD‐MDE was both the strongest predictor of the 3‐month outcome in univariable analyses and had the highest mediator RRs at both 2 and 8 weeks. These results are consistent with prior research showing that comorbid MDE is a strong predictor of PTSD persistence and severity (Pozzato et al, 2020; Schindel‐Allon et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, pre‐MVC lifetime comorbid probable PTSD‐MDE was both the strongest predictor of the 3‐month outcome in univariable analyses and had the highest mediator RRs at both 2 and 8 weeks. These results are consistent with prior research showing that comorbid MDE is a strong predictor of PTSD persistence and severity (Pozzato et al, 2020; Schindel‐Allon et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Although it is known that prior history of posttraumatic stress disorder (PTSD; Beliveau et al, 2019; Breslau et al, 2008; Kessler et al, 2018) and major depressive episode (MDE; Bedaso et al, 2020; Heron‐Delaney et al, 2013) both strongly predict adjustment after subsequent traumas (Ikin et al, 2010; Pozzato et al, 2020) and are highly comorbid (Kenardy et al, 2018), a better understanding of these associations is needed to inform early intervention targeting. Are these histories important because they are associated with peritraumatic symptoms that can be assessed in the immediate aftermath of a subsequent trauma?…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that a number of sociodemographic variables (most notably, sex, race-ethnicity, and socioeconomic status) and diverse indicators of trauma severity predict anxiety and depression in the aftermath of trauma exposure (Hruska, Irish, Pacella, Sledjeski, & Delahanty, 2014;Kazantzis et al, 2012;Lowe, Sampson, Gruebner, & Galea, 2015;Pozzato et al, 2020a;Tang, Liu, Liu, Xue, & Zhang, 2014). An important aim of the current study is to examine whether these variables predict depression 8 weeks after an MVC.…”
Section: Introductionmentioning
confidence: 94%
“…This focus on depression is important because even though depression is significantly elevated post-trauma (Breslau, Davis, Peterson, & Schultz, 2000;Fergusson, Horwood, Boden, & Mulder, 2014;Pozzato et al, 2020a), the emphasis of most posttrauma studies is on PTSD. Importantly, there are ongoing debates whether post-traumatic predictors of depression and PTSD are the same or different (Breslau et al, 2000;McFarlane & Papay, 1992;Tracy, Norris, & Galea, 2011), an issue we will address in future AURORA analyses and that was examined recently by Pozzato et al (2020a), who found high rates of co-occurrence and evidence for shared vulnerability factors in participants recruited within 28 days after an MVC and followed for one year (see also Pozzato et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, psychological factors including depression, anxiety, catastrophic beliefs about pain, low expectations of recovery, and heightened levels of distress have also been shown to be associated with persistent pain [16,26,29,34]. Although these factors are often reported to occur after severe injuries [28], they can also feature in benign injuries such as an ankle inversion injury [30,36], suggesting injury severity is not the prevailing factor underlining adverse and persistent psychological sequelae. Research on the experience of peri-or posttraumatic distress has been increasing because of its potential role in persistent pain from musculoskeletal injury.…”
Section: Introductionmentioning
confidence: 99%